Time synchronization algorithm based on mobility model for underwater sensor networks - qiang WANGHui; xiu WENXiu; yu LINJun; sheng FENGGuang; wu LYUHong (Tongxin xuebao)
With the characteristics of high transmission delay and mobility, distributed time synchronization of underwa-ter sensor networks can be very challenging. The existing works cannot get high accuracy, because most of them ignore the long transmission latency, or dynamic changing tra ission delay caused by the mobility. A mobility model was built considering the effect of mobility and long transmission latency on time synchronization, and a time synchronization parameters equation was formed according to the mobili model. Thus, based on the equation, a time synchronization algorithm (MM-sync) was proposed. The experiment results show that MM-sync can reduce the consumption of energy, and can get higher accuracy than state-of-art solutions in high density underwater sensor networks with rapid movement.